Analysis Of Interpersonal Communication Styles Of PPL Students In The Learning Process Towards Students' Learning Motivation - Sinaga, Anggun Tiur Ida; Sitorus, Yeyen Friskila; Surbakti, Rini br.; Situmorang, Prita; Simbolon, Feky Marshanda; Gultom, Indah Vanessia; Abather Saadoon (CV Putra Publisher, 2026)
This study aims to obtain information regarding 1) motivation and job satisfaction 2) the influence of motivation and job satisfaction on the discipline of educators. The type of research used is quantitative research. Data analysis techniques in this study are descriptive statistics and regression analysis. The results of this study indicate that: 1) there is a significant influence between motivation on the discipline of educators 2) there is a significant influence between job satisfaction on the discipline of educators; 3) there is a significant influence between motivation and job satisfaction on the discipline of educators in Vocational High Schools